Determining key catchments for litter trap installation in urban rivers using a GIS-based approach - Gonlag, Shaidan (Department of Biological Sciences, 2024)
Litter generated in urban centres has fast become a major problem across the world and poses risks to economic, human and environmental health. It is estimated that around 2.0 billion tonnes of solid waste are produced per year. Rivers and stormwater drainage systems are the primary mechanism through which urban litter is transported into the ocean. In South Africa, widespread littering coupled with poor waste management in many communities results in large amounts of litter entering river systems. South Africa has an extremely diverse socio- economic landscape that results in many challenges, both socio-economically and environmentally. Strategies around waste management must be well-informed, locally applicable and data driven if they are to make a significant impact on reducing urban litter loads. Currently, there are few data on the input and magnitude of urban litter entering into river systems. Measurements of daily litter accumulation rates along urban streets in low, medium and high-income suburbs in Cape Town were modelled using a GIS approach to estimate the amount of plastic litter produced across the different hydrological catchments. There was an inverse relationship between income level and daily street litter generation rate in residential areas. The low-income site generated an order of magnitude more litter daily than the high–income site, with the mid-income site having an intermediate value. The model predicted that on average 26.0 (15.3–36.6) tonnes∙day–1 of litter is produced in Cape Town with 56% of this litter being loaded into three major river networks; Salt/Black, Eerste and Diep Rivers. Distribution of current litter traps in the city was poorly correlated (R2 = 0.28) to the catchments receiving the largest plastic litter weight daily. The findings from this study will help better inform the City of Cape Town management with regards to focusing their urban litter mitigation efforts. The approach used could be readily applied in other urban areas to determine weights of urban litter loads and identify key areas for litter trap interventions. Key words: GIS, Plastic, Catchment delineation, Street litter, Litter traps